De l’affirmation d’une distribution alimentaire connectée - Samuel Deprez (Netcom)
Having long been a low key affair but made popular over the last few years with the success of leading retailers’ click and drive facilities, connected grocery retailing is now firmly established in the shopping habits of households and has modified their “supply world”. From online supermarkets to sales between individuals, it has taken on myriad forms according to the actors initiating the value systems that support them. They are all different and each one illustrates the nature of the changes introduced by digital technology in this sector and at their level represent an expression of the “Internet convention”. The example of farm click and drives is used here to put forward a territory-based reading of food e-commerce taking place in the commercial sphere, modifying purchasing practices and the relationship to traditional channels of grocery retailing.